No net loss for people and biodiversity. Issue 1 (2nd August 2018) - Griffiths, Victoria F.; Bull, Joseph W.; Baker, Julia; Milner‐Gulland, E.J.
Abstract: Governments, businesses, and lenders worldwide are adopting an objective of no net loss (NNL) of biodiversity that is often partly achieved through biodiversity offsetting within a hierarchy of mitigation actions. Offsets aim to balance residual losses of biodiversity caused by development in one location with commensurate gains at another. Although ecological challenges to achieve NNL are debated, the associated gains and losses for local stakeholders have received less attention. International best practice calls for offsets to make people no worse off than before implementation of the project, but there is a lack of clarity concerning how to achieve this with regard to people's use and nonuse values for biodiversity, especially given the inevitable trade‐offs when compensating biodiversity losses with gains elsewhere. This is particularly challenging for countries where poor people depend on natural resources. Badly planned offsets can exacerbate poverty, and development and offset impacts can vary across spatial‐temporal scales and by location, gender, and livelihood. We conceptualize the no‐worse‐off principle in the context of NNL of biodiversity, by exploring for whom and how the principle can be achieved. Changes in the spatial and temporal distribution of biodiversity‐related social impacts of a development and its associated offset can lead to social inequity and negatively impact people's well‐being. The level of aggregation (regional, village, interest group, household, and individual) at which these social impacts are measured and balanced can again exacerbate inequity in a system. We propose that a determination that people are no worse off, and preferably better off, after a development and biodiversity offset project than they were before the project should be based on the perceptions of project‐affected people (assessed at an appropriate level of aggregation); that their well‐being associated with biodiversity losses and gains should be at least as good as it was before the project; and that this level of well‐being should be maintained throughout the project life cycle. Employing this principle could help ensure people are no worse off as a result of interventions to achieve biodiversity NNL. Abstract : Article impact statement : That people are no worse off after development and biodiversity offsetting should be based on affected people's perceptions and maintained well‐being.